Horizontal Transfer of Non-LTR Retrotransposons from Arthropods to Flowering Plants. (23rd October 2017) - Gao, Dongying; Chu, Ye; Xia, Han; Xu, Chunming; Heyduk, Karolina; Abernathy, Brian; Ozias-Akins, Peggy; Leebens-Mack, James H; Jackson, Scott A
Abstract: Even though lateral movements of transposons across families and even phyla within multicellular eukaryotic kingdoms have been found, little is known about transposon transfer between the kingdoms Animalia and Plantae. We discovered a novel non-LTR retrotransposon, AdLINE3, in a wild peanut species. Sequence comparisons and phylogenetic analyses indicated that AdLINE3 is a member of the RTE clade, originally identified in a nematode and rarely reported in plants. We identified RTE elements in 82 plants, spanning angiosperms to algae, including recently active elements in some flowering plants. RTE elements in flowering plants were likely derived from a single family we refer to as An-RTE. Interestingly, An-RTEs show significant DNA sequence identity with non-LTR retroelements from 42 animals belonging to four phyla. Moreover, the sequence identity of RTEs between two arthropods and two plants was higher than that of homologous genes. Phylogenetic and evolutionary analyses of RTEs from both animals and plants suggest that the An-RTE family was likely transferred horizontally into angiosperms from an ancient aphid(s) or ancestral arthropod(s). Notably, some An-RTEs were recruited as coding sequences of functional genes participating in metabolic or other biochemical processes in plants. This is the first potential example of horizontal transfer of transposons between animals and flowering plants. Our findings help to understand exchanges of genetic material between the kingdom Animalia and Plantae and suggest arthropods likely impacted on plant genome evolution.